Analisis Kemampuan Numerasi Siswa Sekolah Dasar - Fatmawati (*), Risdiana Andika; Nurdiana, Riyanti; Suriyana, Suriyana (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2025)
Numeracy is the knowledge and skills to use various kinds of numbers and symbols related to basic mathematics to solve practical problems in a variety of daily life contexts and analyze information displayed in various forms (graphs, tables, charts, etc.) and then use the interpretation of the results of the analysis to predict and make decisions. researchers want to contribute to schools by analyzing the literacy and numeracy skills of students from three indicators of literacy and numeracy skills. This research uses qualitative methods. Data collection techniques with tests and observations. The results showed that the numeracy skills of SDN 25 Sungai raya students were still in the low category. The first indicator is in the low category, the second and third indicators are in the very low category. The conclusion obtained in this study is that students of SDN 25 Sungai Raya are lacking in high-level thinking. The ability to think at this level is not instantly obtained, but must be trained. One form of training is to familiarize students with higher order thinking in every learning activity.